Pembentukan Akhlak Al-Karimah pada Anak Usia Dini - Achmad Junaedi (Universitas Al-Hikmah Indonesia, 2018)
This research is based on the preparation of akhlak al-karimah in children should be given as early as possible. What is meant by this research is to know the concept of akhlak al-karimah formation at the early time of study according to study of Islamic education. this research hoped can formulate the concept of akhlak al-karimah development in early childhood in the family according to Islamic Education study which includes: understanding, purpose, function, characteristics of preschool children, parents, supporting factors and stages of formation akhlak al-karimah. By using the literature method and the available data from the literature, it is found that the establishment of educational institutions through guidance, habituation, direction and guidance and good practices between human and community environment in accordance with the pious nature of the foundation with the values Islam contained in Al-qur`an and Al-Hadith.